Comparison of liquid-based cytology cervical smears with histopathological findings - (:unkn) unknown (DERMAN MEDICAL PUBL, 2018)
Aim: Cervical cancer is still a health problem in countries where cervical cancer screening is not routinely performed. A significant decrease in the rate of mortality from cervical cancer has been observed since the Pap test was introduced. Within the last decade liquid-based cytology (LBC) has replaced the Pap test. Our aim is to compare cervical smears prepared with the liquid-based cytology method with histopathological findings. Material and Method: Cervical smears and corresponding cervical biopsy reports of 300 patients diagnosed with epithelial cell abnormality between 2014-2016 were reevaluated retrospectively. Smears were prepared with the LBC test SurePath. Biopsy materials were stained with hematoxylin eosin. Slides were reported according to Bethesda 2014 classification. Biopsy materials were classified into 4 categories according to the WHO 2014 classification. Results: Cytology results of 273 patients (91%) were abnormal. Biopsy results showed lesions such as low grade cervical intraepithelial lesion, high grade cervical intraepithelial lesion, and squamous cell carcinoma in 178 patients (59.3%). The calculated sensitivity and specificity for LBC were 89.89% and 7.38% respectively, indicating low accuracy of specificity for LBC. Discussion: The management of treatment in diagnosis of epithelial cell abnormality in cervical cytology should be according to the sets of specified protocols. Because we may encounter high grade squamous intraepithelial lesions in biopsy with the diagnosis of atypical squamous cells of undetermined significance (ASCUS) in cytology, the necessity of colposcopy can be disputed for the management of this group of lesions.
Keywords: 2014 Bethesda System; Cervical Cancer; Liquid-Based Cytology; CONSENSUS GUIDELINES; CANCER; ABNORMALITIES; COLPOSCOPY; MANAGEMENT; WOMEN